DETERMINANTS OF CONSUMER PARTICIPATION IN BOYCOTTS OF PRO-ISRAELI PRODUCTS: EVIDENCE FROM INDONESIA - Zahra, Qiny Shonia Az; Nurhasanah, Elis; Aisyah, Iis (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: This study explores the determinants of consumer boycott participation of pro-Israel products in Indonesia, a context in which political conflicts strongly shape consumption behavior. Design/Methodology/Approach: A quantitative descriptive method was used, data collection was conducted in 2024 using purposive sampling technique involving 230 respondents and used Structural Equation Modeling, specifically Partial Least Squares (SEM-PLS), to examine how religiosity, consumer animosity, and consumer affinity affect boycott actions. Research findings: The findings revealed that consumer animosity was the strongest predictor of boycott participation (β = 0.619, p < 0.001). In contrast, religiosity (β = –0.024, p = 0.641) and consumer affinity (β = 0.173, p = 0.090) did not have significant effects. The R-square of the boycott participation variable was 0. 558.The results highlight that socio-political emotions, especially animosity, influence boycott behavior more than religious beliefs. Theoretical Contribution/Originality: This study adds to the consumer behavior field by focusing on actual participation instead of just intentions, showcasing evidence from an emerging economy. Practitioners/Policy Implications: Socio-political content-based public awareness campaigns through social media and influencers, and providing databases or applications that contain a list of products affiliated with Israel, can be a practical strategy to build more consistent and impactful boycott participation. Research Limitations/Implications: This study is limited by the concentration of respondents in Java, which may not fully capture the diversity of consumer behavior across Indonesia. Future research should expand the sample to other regions to provide more representative insights.